Pengaruh Inovasi Produk, Kualitas Layanan, Minat Konsumen, Dan Keunggulan Bersaing Terhadap Kepuasan Pelanggan Pada Usaha Mebel (Study Kasus Toko Istana Kado Merapi) - Nabila, Ausaf Yoan; Suryadi, Suryadi (Jurnal Manajemen DIVERSIFIKASI, 2022)
In the current era of globalization has entered a very competitive and very strong condition, every year the business environment is unpredictable and market demands change a lot. This allows business people to implement strategies in their business to maintain the viability and competitiveness of the company. These companies try to execute customer satisfaction in order to get big profits and try to get as much customer loyalty as possible in different ways. This study aims (1) to determine whether product innovation has a significant effect on customer satisfaction (2) to determine whether service quality has a significant effect on customer satisfaction (3) to determine whether consumer interest has a significant effect on customer satisfaction (4) to determine whether competitive advantage significant effect on customer satisfaction (5) To determine whether product innovation, service quality, consumer interest, competitive advantage have a significant effect on customer satisfaction. The survey method focuses on collecting data from respondents who have certain information, thus enabling researchers to solve problems. Data collection was carried out using a questionnaire or questionnaire instrument. The population in this study are customers who buy goods at the Merapi Gift Palace shop, consumers who buy in June to December as many as 325 consumers. The results showed that (1) there is a positive effect of product innovation on customer satisfaction (2) there is a positive influence of service quality on satisfaction (3) there is a positive influence of consumer interest on customer satisfaction (4) there is a positive influence of competitive advantage on customer satisfaction (5) there is a positive effect of product innovation, service quality, consumer interest, competitive advantage on customer satisfaction. Keywords: Product Innovation, Service Quality, Consumer Interest, Competitive Advantage Customer Satisfactio